Eksplorasi Model Kewirausahaan Berkelanjutan UMKM Melalui Peran Gender dalam Meningkatkan Ketahanan Pangan: Model Kewirausahaan, Berkelanjutan, UMKM, Gender, Ketahanan Pangan - Indah, Sri; Sulistyowati, Yayuk (Jurnal Paradigma Ekonomika, 2025)
The purpose of this research is to explore sustainable entrepreneurship models in the food MSME sector by highlighting the role of women. The main focus of this research is to identify the obstacles and supporting factors in the development of gender-based food MSMEs and to analyse women's contribution to food security in the Greater Malang area. Additionally, this research aims to examine empowerment strategies for women that can enhance business sustainability and provide policy recommendations to support more inclusive economic growth. The research methodology employs a mixed-method approach to achieve a more in-depth analysis. Qualitative data was collected through in-depth interviews with food SME stakeholders, while quantitative data was obtained through surveys to assess factors influencing business sustainability and food security. The research findings indicate that the role of gender in food SME entrepreneurship has a significant positive impact on local food security. Gender roles in food SME entrepreneurship influence local food security through women's empowerment strategies. Women's empowerment strategies act as mediating variables that strengthen the relationship between gender roles and food security. The more effectively women's empowerment strategies are implemented, the greater the positive influence of gender-based entrepreneurship on local food security.